Determinação simultânea dos ácidos orgânicos tartárico, málico, ascórbico e cítrico em polpas de acerola, açaí e caju e avaliação da estabilidade em sucos de caju - Scherer,Rodrigo (2008)
The aim of the present study was determining the main organic acids in pulp and juices, as well as evaluating their stability, after opening the package, by liquid chromatography in a C18 column with isocratic elution and UV detection. In açaí pulp tartaric, malic and citric acids were found. Cashew samples presented all of the organic acids evaluated, besides high concentrations of ascorbic and malic acids. Acerola pulp had the highest ascorbic acid concentration. A small decrease in organic acid content during storage was observed. Malic and citric acids seem to be more stable than tartaric and ascorbic acids.